JARINGAN SYARAF TIRUAN UNTUK PREDIKSI PENJUALAN JAMUR MENGGUNAKAN ALGORITMA BACKROPAGATION - Yuyun Dwi Lestari (Journal Information System Development, 2017)
This study predicts sales of Jamur by applying Artificial Neural Network. Aplication using Backpropagation algorithm where input data is the amount sold, income and expenditure. Then the formed Neural Network to determine theunit of each layer. After network was formed conducted training of the data has been grouped. Experiments were performed with a network architecture that consists of input units, hidden unit, unit output and network architecture 3-3-1.  Testing is done using software Matlab.  Keywords : predict, Neural Network, sale, backpropagation